2008
DOI: 10.1159/000138901
|View full text |Cite
|
Sign up to set email alerts
|

First prenatally detected small supernumerary neocentromeric derivative chromosome 13 resulting in a non-mosaic partial tetrasomy 13q

Abstract: Neocentromeres are functional centromeres located in non-centromeric euchromatic regions of chromosomes. The formation of neocentromeres results in conferring mitotic stability to chromosome fragments that do not contain centromeric alpha satellite DNA. We present a report of a prenatal diagnosis referred to cytogenetic studies due to ultrasound malformations such as large cisterna magna, no renal differentiation, hypotelorism and ventriculomegaly. Cytogenetic analysis of GTG-banded chromosomes from amniotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…In these neocentric sSMC 13q, four distinct regions have been found to contain neocentromeres: 13q21 (five cases) [Tohma et al, 1998; Morrissette et al, 2001; Li et al, 2002; Knegt et al, 2003; Dhar et al, 2009], 13q31 (five cases) [Tohma et al, 1998; Barwell et al, 2004; Tonnies et al, 2006; Liehr et al, 2007; Mascarenhas et al, 2008], 13q31/32 (one case) [Amor et al, 2005] and 13q32 (seven cases) [Depinet et al, 1997; Lozzio et al, 1997; Warburton et al, 1997; Govaerts et al, 1999; Rivera et al, 1999; Li et al, 2002] (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…In these neocentric sSMC 13q, four distinct regions have been found to contain neocentromeres: 13q21 (five cases) [Tohma et al, 1998; Morrissette et al, 2001; Li et al, 2002; Knegt et al, 2003; Dhar et al, 2009], 13q31 (five cases) [Tohma et al, 1998; Barwell et al, 2004; Tonnies et al, 2006; Liehr et al, 2007; Mascarenhas et al, 2008], 13q31/32 (one case) [Amor et al, 2005] and 13q32 (seven cases) [Depinet et al, 1997; Lozzio et al, 1997; Warburton et al, 1997; Govaerts et al, 1999; Rivera et al, 1999; Li et al, 2002] (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Marker chromosomes are abnormal chromosomes formed by rearrangements or amplifications of specific genomic regions. Phenotypes associated with marker chromosomes stabilized by neocentromeres include: facial dysmorphisms, renal defects, short stature, and developmental delays (Mascarenhas et al, 2008, Burnside et al, 2011). Prenatal identification of neocentric marker chromosomes can be achieved by cytogenetic analysis of chromosomes from amniotic fluid and fetal blood cells (Mascarenhas et al, 2008).…”
Section: Neocentromeres In Human Healthmentioning
confidence: 99%
“…More than 10 neocentromeric sSMCs originating from the distal region of chromosome 13q were summarized by some studies Mascarenhas et al, 2008;Ewers et al, 2010], with one of them, which showed a similar duplicated size as the sSMC in case 12, identified prenatally.…”
Section: Mechanisms Leading To the Formation Of The Ssmcsmentioning
confidence: 99%